Ginsenoside Rh2 mitigates doxorubicin‐induced cardiotoxicity by inhibiting apoptotic and inflammatory damage and weakening pathological remodelling in breast cancer‐bearing mice. Issue 6 (9th May 2022) - Hou, Jingang; Yun, Yeejin; Cui, Changhao; Kim, Sunchang
Abstract: Objectives: There are presently a few viable ways to reduce cardiotoxicity of doxorubicin (Dox). The combination of chemotherapy agents with natural compounds delivers greater efficacy and reduces adverse effects in recent researches for cancer treatment. Here, we examined the potential effect of ginsenoside Rh2 on a Dox‐based regimen in chemotherapy treatment. Materials and Methods: Human breast tumour (MDA‐MB‐231) xenograft nude mice, human cardiac ventricle fibroblasts, and human umbilical vein endothelial cells (HUVEC) were employed in the present study. Histology, immunohistochemistry, immunofluorescence, western blot, antibody array, and RNA‐sequencing analyses were utilized to assess the protective effect of Rh2 on cardiotoxicity induced by Dox and the underlying mechanisms. Results: Rh2‐reduced cardiotoxicity by inhibiting the cardiac histopathological changes, apoptosis and necrosis, and consequent inflammation. Pathological remodelling was attenuated by reducing fibroblast to myofibroblast transition (FMT) and endothelial–mesenchymal transition (EndMT) in hearts. RNA‐sequencing analysis showed that Dox treatment predominantly targets cell cycle and attachment of microtubules and boosted tumour necrosis, chemokine and interferon‐gamma production, response to cytokine and chemokine, and T cell activation, whereas Rh2 regulated these effects. Intriguingly, Rh2 also attenuated fibrosis via promoting senescence in myofibroblasts and reversing established myofibroblast differentiation in EndMT. Conclusions: Rh2 regulates multiple pathways in the Dox‐provoked heart, proposing a potential candidate for cancer supplement and therapy‐associated cardiotoxicity. Abstract : Doxorubicin is extensively reported to induce severe cardiotoxicity in clinical applications. Our work proposed a natural herbal compound, ginsenoside Rh2, as a potential candidate for attenuating this side effect. Rh2 significantly inhibited cardiac apoptosis and necrosis, inflammation, and pathological remodelling in Dox‐challenged hearts.